Cost-effectiveness of mental health promotion and prevention for young people: a systematic review. (13th November 2019) - Schmidt, M; Werbrouck, A; Verhaeghe, N; Putman, K; Simoens, S; Annemans, L
Abstract: Background: Effective mental health promotion and mental disorder prevention interventions may reduce the impact that mental health problems have on young people's wellbeing. The objectives of this research were to summarize and assess health economic evaluations of mental health promotion and prevention for children and adolescents aged 6-18 years. Methods: Four electronic databases were searched for full health economic evaluations published between January 1, 2013 and October 31, 2018 that evaluated the cost-effectiveness of universal mental health promotion and primary mental disorder prevention interventions. Each study was subject to a systematic quality-appraisal. Results: Nine studies were included. Eight were carried out in the European Union, and eight evaluated school-based interventions. All evaluated interventions led to incremental costs compared to their comparators and most were associated with small increases in quality-adjusted life years. Four studies evaluated the cost-effectiveness of cognitive behavioural therapy-based interventions for the prevention of depression or anxiety, with mixed results. Cost-effectiveness estimates for mental health promotion and anti-bullying interventions were promising. Drivers of cost-effectiveness were implementation costs, intervention effectiveness, delivery mode and duration, baseline prevalence, and the perspective of the evaluation. The overall study quality was reasonable, though most studies only assessed short-term costs and effects. Conclusions: Few studies were found. This limits the possibility of drawing strong conclusions about cost-effectiveness. There is some evidence based on decision-analytic modelling that anti-bullying interventions represent value for money. There is a lack of studies that take into account long-term costs and effects. Key messages: Based on the evidence, schools should be supported in the implementation of long-term anti-bullying programmes to improve young people's wellbeing. More research is needed on the long-term costs and effects of mental health promotion and prevention for children and adolescents.